Analisis Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan pada Platform Investasi Crownfunding berbasis Mobile - Ardhityar Izaaz S; Rinabi Tanamal (International Consortium of Education and Culture Research Studies, 2019)
Investment is planting of assets carried out by company or individual. One of investment model is crowdfunding where collecting funds from large community so that significant funds are collected. Crowdfunding is managed by mobile application platform so that make easily accessed. To make customer investment, it is necessary through an investment provider. One of the important things of investment provider is service quality. Sometimes investment provider companies have problem in knowing the factor that can increase customer satisfication. This can make the company wrong in providing services needed by its customer.To find out the level of investor satisfication an analyse of factor that influence satisfication can be done. Factor of service quality can be used in the analyse. In service quality there are several factor namely tangibels, reliability, responsiveness, assurance and emphaty. In analysing used SPSS software to see the influence of these factors. After conducting research shows that service quality can affect customer satisfication, especially in the variables of reliability, responsiveness and tangibels that have significant influence. For the assurance and emphaty variables, they have an influence but not significantly. Therefore crowdfunding investment platform can implement aspects of service quality to influence their investor satisfication.